Exploring Model-to-Model Transformations for RIA Architectures by means of a Systematic Mapping Study - Bonhaure Falcón, Daniel Pierre (2017)
This study focuses on model-to-model – M2M – transformations, as part of the Model- Driven Development – MDD – approach, for Rich Internet Applications – RIA. The main aim of this study is to identify fields that require further contributions, and/or research opportunities in the previously mentioned context. We applied mapping studies techniques, since these techniques use the same basic methodology as reviews but are more general and aimed at discovering what the research trends are, allowing to identify gaps in the literature. From an initial set of 132 papers, we selected 30 papers first. Then, thanks to experts’ suggestion, we added 3 additional papers. Therefore, we considered 33 research papers. The performed analysis led to various considerations. Among the important ones, we can mention: there are many newly proposed methods, the scarcity of rigorous and formal validation of such methods, the problem of the portability of Platform Independent Models – PIM, and the low number of tools available for MDD.